2011
DOI: 10.1007/s00270-011-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Retrograde Sclerotherapy for Refractory Bleeding of Jejunal Varices: Direct Injection via Superficial Epigastric Vein

Abstract: Small-bowel varices are rare and almost always occur in cases with portal hypertension. We encountered a patient with bleeding jejunal varices due to liver cirrhosis. Percutaneous retrograde sclerotherapy was performed via the superficial epigastric vein. Melena disappeared immediately after treatment. Disappearance of jejunal varices was confirmed by contrast-enhanced computed tomography. After 24 months of follow-up, no recurrent melena was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The selection of possible therapeutic options is made considering the risks and benefits based on the site of the varices, patient’s condition, doctor’s experience, and the capability of the facility [ 15 ]. Therapeutic options for bleeding ectopic varices include local treatment for the varices and portal decompression [ 16 ]. Local treatment for the varices comprise endoscopic sclerotherapy, endoscopic variceal band ligation, endoclips, percutaneous transhepatic obliteration, and balloon-occluded retrograde transvenous obliteration.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of possible therapeutic options is made considering the risks and benefits based on the site of the varices, patient’s condition, doctor’s experience, and the capability of the facility [ 15 ]. Therapeutic options for bleeding ectopic varices include local treatment for the varices and portal decompression [ 16 ]. Local treatment for the varices comprise endoscopic sclerotherapy, endoscopic variceal band ligation, endoclips, percutaneous transhepatic obliteration, and balloon-occluded retrograde transvenous obliteration.…”
Section: Discussionmentioning
confidence: 99%
“…El tratamiento endoluminal se ha descrito para el control del sangrado las asas de nailon (miniloops) que permiten ligar la várice, y también se han instilado directamente a la VE el cianoacrilato con controles temporales del sangrado (37,38).…”
Section: Tratamiento De Las Várices Ectópicas (Ve)unclassified
“…Even with a micropuncture set, however, percu taneous access may be challenging (Fig 13). Mi nami et al (74) have reported a cutdown technique for access to the left superficial epigastric vein to perform BRTO for stomal varices, and Nakata et al (75) have recently used a similar access route for sclerotherapy of jejunal varices. If a sclerosant is used, fluoroscopy-guided compression over drainage veins can decrease early outflow into the systemic system.…”
Section: Ectopic Varices: Percutaneous Access and Sclerotherapymentioning
confidence: 99%